French-Canadian translation, cultural adaptation, and preliminary evaluation of the wheelchair service provision – basic test validity among occupational therapy students. (2nd January 2023) - Rushton, Paula W.; Kawish-Arbelaez, Diana; Levac-Marquis, Annabelle; Fung, Karen; Daoust, Geneviève; Ishack, Michelle; Goldberg, Mary; Pearlman, Jon
Abstract: Purpose: The objectives were: (1) to translate and adapt the International Society of Wheelchair Professional (ISWP) basic Wheelchair Service Provision Test (bWSPT) into French-Canadian and (2) to conduct a preliminary evaluation of the French-Canadian version of the ISWP bWSPT internal consistency and relations with other variables among French-Canadian occupational therapy students. Methods: For Phase 1, based on the International Test Commission Guidelines for Translating and Adapting Tests, a forward translation and adaptation from English to French-Canadian was conducted by a translation team. For Phase 2, the validity evidence of the French-Canadian bWSPT was evaluated through internal consistency and comparison of bWSPT scores and final grades of a wheelchair-specific course with a sample of occupational therapy students (positive, moderate correlation hypothesized). Internal consistency was measured with Cronbach's α . The correlation was calculated using the Spearman's Rank Correlation Coefficient. Results: For phase 1, 61 of 167 items of the forward adaptation were revised and modified. All revisions were a consensus by the translation team. For phase 2, we found a Cronbach's α of 0.50 and a correlation of ⍴ = 0.27 ( p  = 0.43) between the bWSPT French-Canadian version and the wheelchair-specific course final grade. The low variability of the data may explain the lower-than-expected correlation. Other possible data-driven reasons have been explored using post-hoc analysis. Conclusion: The ISWP bWSPT, French-Canadian version, is not internally consistent and demonstrates a non-statistically significant, positive, weak correlation with the final grade of a wheelchair service provision-specific course among a cohort of 35 occupational therapy students. IMPLICATIONS FOR REHABILITATION: The lack of adequately educated wheelchair service providers is a contributing factor to inappropriate wheelchair provision worldwide. The ISWP Wheelchair Service Provision Basic Test (ISWP bWSPT) has been created to evaluate competency among wheelchair service providers and provides a standardized test recognized internationally. A French-Canadian version of the ISWP bWSPT allows competency testing of French-speaking wheelchair service providers across Canada. This study shows that the French-Canadian version of the test is not internally consistent and has a low correlation with a wheelchair provision-specific course among a cohort of 35 occupational therapy students at a French-Canadian university suggesting further refinement is required to improve its measurement properties in this population of test-takers.